Derivation of Yang -Mills equations from Maxwell Equations and Exact solutions - Gharib, Gharib Mousa (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper we derived the Yang-Mills equations from Maxwell equations. Consequent-ly we find a new form for self-duality equations. In addition exact solution class of the classical SU(2) Yang-Mills field equations in four dimensional Euclidean space and two exact solution classes for SU(2) Yang- Mills equations when is a complex analytic function are also obtained.